Parameters Modeling and Probing of Highway Structural Deterioration: Case study of F-209 Segment of Ondo - Ore Pavement, Southwestern Nigeria - Olumuyiwa Olusola Falowo (MO.RI Publishing, 2023)
The construction of highway route is influenced by geology, geotechnical, topography, and geomorphology of the terrain. However, for pavement that failed structurally, a critical investigation is required to ascertain the cause(s) of its failure, so that such study can assist during the rehabilitation/re-construction phase. Based on this, the incessant failed Ondo – Ore was studied using integrated methods. Electrical resistivity involving four vertical electrical sounding, ten dynamic cone penetration test, three coring by trial pits at 1.0 to 3.0 m offset from the edge of the highway at different chain-age, and laboratory geotechnical-geochemical analysis adopting standard procedures. The VES characterized the geological sequence within the highway alignment to be topsoil, subsoil, weathered layer, and basement rock. The topsoil/subsoil and the weathered layer on which the highway is founded is sandy clay and clay with resistivity less than 200 ohm-m. The depths to basement ranged from 33.5 to 45.1 m. The trial pits recordings are consistent with the results of the VES, geotechnical, and geochemical analysis, distinctly distinguishing the upper 1 m into clayey soil (sandy clay, clayey hardpan) laterite, and silt-clay-sand mixture. The engineering competence of the topsoil/subsoil on which the road is founded is poor, although is inactive SC-SM, A-7-5/A-7-6 lateritic soil type (silica-sesquioxide ratio of 1.67). The clay mineralogy is within the illite – montmorillonite group. The SNG, SN, and SNP contributions of the soil as subgrade, subbase, and base material are very low (<1.0). The regression models of all parameters correlated positively, although weak for RD and DCPI, in-situ CBR and MR, RD and in-situ CBR; while strong for soaked CBR and in-situ CBR, ER and MR. Consequently, based on the GI and CBR values, the expected average thickness of the highway should range between 191 mm (good segment) to 445 mm (for weak segment) (avg. 312 mm) which is far thicker than 274 mm measured along the highway alignment during reconnaissance survey. Therefore, it can be concluded that the failure of the highway is as a result of low soaked CBR/in-situ CBR values with low strength coefficient; and low design thickness across the highway. In addition, lack of drainage at the shoulders of the highway is also causative factor. Hence, the need for effective design of roads (to specification) and maintenance strategy was therefore advocated.